NOMINA DEVERBAL DALAM BAHASA JAWA BANYUMAS - Bagiya Bagiya Bagiya (p-ISSN 2356-0576, 2017)
Abstract: In Javanese Banyumas language, it is found a change of verbal becoming nominal so called nominal deverbal. The affixes maker of transposition from verb to noun in Javanese Banyumas language are: prefix pe- and peN-, sufix –an, confix pa-an, peN-an, and ke-an.     Abstrak: Dalam bahasa Jawa Banyumas ditemukan proses perubahan kelas kata dari verba menjadi nomina yang disebut nomina deverbal. Afik pembentuk nomina deverbal dalam bahasa Jawa Banyumas dapat berupa: prefiks pe- dan peN-, sufiks –an, konfiks pa-an, peN-an, dan ke-an.